Engagement with school in Gypsy students attending school in Portugal. Issue 2 (4th March 2022) - Moreira, Paulo A. S.; Bilimória, Helena; Lopes, Sandra
ABSTRACT: Gypsy students are vulnerable to poor school attendance, low achievement, and school dropout (indicative of low engagement with school). Engagement with school is a multidimensional construct with cognitive, affective, and behavioural components, and research has yet to fully characterise engagement among Gypsy students considering these distinct dimensions. Towards this aim, Gypsy ( n = 42) and non-Gypsy students ( n = 76) completed the Student Engagement Instrument, which measures cognitive indicators of engagement and perceptions of support for learning from peers, parents, and teachers. Gypsy students had significantly less cognitive engagement with school, and perceived lower family support for learning, than non-Gypsy students. Gypsy and non-Gypsy students were highly similar in perceived support from teachers and peers. This more detailed characterisation of Gypsy student engagement has implications for intervention practice and policy aimed at promoting educational equity for minority groups.